Adding some context to port marketing: Exploring the content and measurement of market orientation in the port industry - Kounoupas, Evangelos; Pardali, Angeliki (SPOUDAI Journal of Economics and Business, 2015)
Understanding and responding to customer needs is the essence of the marketing concept and as such it has been discussed in various fields of business and economic literature. Port economics and management literature has thoroughly investigated areas such as port efficiency and effectiveness, understanding and overcoming competitive pressures and identifying the sources of potential sustainable competitive advantage. In line with this discussion, albeit with a significant time delay, port economics and management literature has also proposed the use of marketing strategies as a strategic tool towards achieving port competitiveness. Applying the marketing philosophy in the port context has been often proposed as a tool towards addressing the above challenges; however there is limited research on that field. This paper attempts to provide a solid theoretical background to the notion, the need and the applicability of the marketing concept in the container port industry. It investigates the preconditions under which port marketing strategies are designed and formulated, by measuring the level of market orientation of ports and terminals based on primary data collected from port executives around the world. Statistical analysis indicates that when production of port services is combined with the regulatory role of a Port Authority, market orientation is comparatively higher. JEL Classification: M 390, R 400